Student Perspective of ACE Website to Complete Presentations in Open and Distance Learning (ODL) - Shanthi Kasawi Krisnan, Alice; a/p Paramasivam, Sheela; Izzah Jamil, Nur; Noor Dina Ahmad, Siti; Nur Fitri bin Mohd Salim, Mohd (International Research in Education, 2022)
Open and Distance Learning (ODL) was adopted by most higher learning institutions when the Covid-19 pandemic hit the world. Its implementation at an unprecedented speed and haste caused difficulties for students, especially those who were not digitally savvy. As such, the ACE website was created to help students overcome their difficulties, especially with regard to completing their English course assignments. It has tools and apps and a step-by-step user guide to create interactive and attractive presentations. Thus, this paper aims to investigate the university students’ perspectives on ACE to help them complete their English course assignments during ODL. A pre-ACE and a post-ACE online questionnaire were administered using non-probability sampling and quota sampling. The total sample size was 186 respondents who completed both the pre-and post-survey. The findings show that most students have positive perceptions of the ability of ACE to help them prepare interactive and attractive presentations. More students rated themselves better after using ACE to imbed slide presentations with video and audio. Post ACE data revealed that students have become better at preparing presentations using PowerPoint and Canva. After using ACE, many students seem to have shifted to the VN video editing app from previously using Filmora. Overall, the study indicates ACE has helped students prepare better presentations for English courses.